2015
DOI: 10.2217/epi.14.91
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BET Bromodomains for Cancer Treatment

Abstract: The bromodomain and extraterminal (BET) subfamily of bromodomain-containing proteins has emerged in the last few years as an exciting, novel target group. BRD4, the best studied BET protein, is implicated in a number of hematological and solid tumors. This is linked to its role in modulating transcription elongation of essential genes involved in cell cycle and apoptosis such as c-Myc and BCL2. Potent BET inhibitors with promising antitumor efficacy in a number of preclinical cancer models have been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 119 publications
2
114
0
Order By: Relevance
“…Inhibition of BRD4, a component of super-enhancers, resulted in a dramatic decrease of c-MYC expression and an impact on cancer cell proliferation (Jung et al, 2015; Loven et al, 2013; Shi et al, 2013). Our finding of RACK7 and KDM5C regulation of super-enhancers suggests that the cancer phenotypes caused by loss of RACK7 and KDM5C might be in part due to overactivation of certain super-enhancers, such as the one located in the S100A Cluster I.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of BRD4, a component of super-enhancers, resulted in a dramatic decrease of c-MYC expression and an impact on cancer cell proliferation (Jung et al, 2015; Loven et al, 2013; Shi et al, 2013). Our finding of RACK7 and KDM5C regulation of super-enhancers suggests that the cancer phenotypes caused by loss of RACK7 and KDM5C might be in part due to overactivation of certain super-enhancers, such as the one located in the S100A Cluster I.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on our overall and progression-free survival curve analyses, prognosis appears to be better correlated with amplification rather than mRNA expression, suggesting a potential collaborative role of co-amplified genes in the amplicons. Despite being a part of amplicons, there are several studies demonstrating the importance of NSD3, CHD8 and BRD4 in oncological processes (27)(28)(29)(30)(31), and it is noteworthy that amplicons may not necessarily contain only one oncogene, but may act as a unit with several genes of importance (26). Future knockdown of NSD3, BRD4 and CHD8 or treatment of HGSC displaying pathway amplification with BRD4-specific small-molecule inhibitors are required to confirm the growth-promoting properties of specific gene amplification in patients with pelvic HGSC.…”
Section: Discussionmentioning
confidence: 99%
“…The BET subfamily of bromodomain-containing proteins is involved in a number of hematological and solid tumors (15,17). Currently, several active clinical trials aiming to treat malignancies are using BET inhibitors, such as FT-1101, ZEN003694, BMS-986158, INCB054329, RVX-208, I-BET 762, OTX 015, CPI-0610, and TEN-010 (www.clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…This led to clinical studies focusing mostly on the treatment of leukemia and lymphoma. As a result of these studies, the first encouraging signs of efficacy have already been reported (17). Furthermore, previous studies showed that BET inhibitors also control neuronal differentiation and cause an autism-like syndrome (18).…”
mentioning
confidence: 82%